A cross-linguistic perspective to classification of healthiness of speech in Parkinson's disease. (August 2022) - Verkhodanova, Vass; Coler, Matt; Jonkers, Roel; Timmermans, Sanne; Maurits, Natasha; de Jong, Bauke; Lowie, Wander
Abstract: People with Parkinson's disease often experience communication problems. The current cross-linguistic study investigates how listeners' perceptual judgements of speech healthiness are related to the acoustic changes appearing in the speech of people with Parkinson's disease. Accordingly, we report on an online experiment targeting perceived healthiness of speech. We studied the relations between healthiness perceptual judgements and a set of acoustic characteristics of speech in a cross-sectional design. We recruited 169 participants, who performed a classification task judging speech recordings of Dutch speakers with Parkinson's disease and of Dutch control speakers as 'healthy' or 'unhealthy'. The groups of listeners differed in their training and expertise in speech language therapy as well as in their native languages. Such group separation allowed us to investigate the acoustic correlates of speech healthiness without influence of the content of the recordings. We used a Random Forest method to predict listeners' responses. Our findings demonstrate that, independently of expertise and language background, when classifying speech as healthy or unhealthy listeners are more sensitive to speech rate, presence of phonation deficiency reflected by maximum phonation time measurement, and centralization of the vowels. The results indicate that both specifics of the expertise and language background may lead to listeners relying more on the features from either prosody or phonation domains. Our findings demonstrate that more global perceptual judgements of different listeners classifying speech of people with Parkinson's disease may be predicted with sufficient reliability from conventional acoustic features. This suggests universality of acoustic change in speech of people with Parkinson's disease. Therefore, we concluded that certain aspects of phonation and prosody serve as prominent markers of speech healthiness for listeners independent of their first language or expertise. Our findings have outcomes for the clinical practice and real-life implications for subjective perception of speech of people with Parkinson's disease, while information about particular acoustic changes that trigger listeners to classify speech as 'unhealthy' can provide specific therapeutic targets in addition to the existing dysarthria treatment in people with Parkinson's disease. Highlights: Acoustic features predict the perceptual judgements of speech healthiness. Phonation and prosody are the best predictors of speech healthiness judgements. Listeners' language background influences the importance of acoustic predictors. Expertise and language background have little influence on prediction accuracy.